2011
DOI: 10.1007/s00406-011-0275-6
|View full text |Cite
|
Sign up to set email alerts
|

The interrelation of needs and quality of life in first-episode schizophrenia

Abstract: The interrelation between needs for care and quality of life has been described and replicated by several studies. The present work aims to add to the understanding of longitudinal interrelations between needs for care, quality of life, and other outcome measures by analyzing a sample of patients at the onset of schizophrenia. This study relied on data from the EUFEST trial, designed to compare first- and second-generation antipsychotics during 1 year. At baseline, 498 patients have been included. The first (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
2
12
1
Order By: Relevance
“…This is consistent with other longitudinal studies done in different clinical samples (Slade et al, 2004;Hansson and Bjorkman, 2007). Moreover, Landolt et al (2012), using a SEM approach in a groups of patients with a first-episode of schizophrenia, found that fewer unmet needs, higher depression, baseline QOL, age and gender (female) were all factors associated with higher QOL at follow-up. In our study, besides service satisfaction and social support, the other predictors of change were longitudinally inconsistent.…”
Section: Longitudinal Findingssupporting
confidence: 90%
“…This is consistent with other longitudinal studies done in different clinical samples (Slade et al, 2004;Hansson and Bjorkman, 2007). Moreover, Landolt et al (2012), using a SEM approach in a groups of patients with a first-episode of schizophrenia, found that fewer unmet needs, higher depression, baseline QOL, age and gender (female) were all factors associated with higher QOL at follow-up. In our study, besides service satisfaction and social support, the other predictors of change were longitudinally inconsistent.…”
Section: Longitudinal Findingssupporting
confidence: 90%
“…In accordance with our first hypothesis, the strongest predictor of SQOL was found to be the severity of needs: the less severe the needs, the higher the SQOL. This result compares with previous studies, which found that unmet needs (serious problems) [24,78-80] had a highly negative impact on SQOL. Findings using the CAN as the needs instrument made a distinction between serious problems, moderate problems and absence of needs [24,47,81,82].…”
Section: Discussioncontrasting
confidence: 73%
“…), with one additional article meeting criteria for Part B, but not Part A (Landolt et al . ). This article was reviewed in the full‐text review of both searches, however, did not report specific needs.…”
Section: Resultsmentioning
confidence: 97%